On the uniqueness of solutions to some boundary-value problems for differential equations in a domain with algebraic boundary - Burskii, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Classes of differential equations with constant coefficients admitting unique solutions of Dirichlet and Cauchy boundary-value problems are considered in a bounded domain with algebraic boundary. For the Dirichlet problem in a ball, the necessary and sufficient conditions for the uniqueness of the solution are obtained in the form of a countable sequence of inequalities polynomial in the coefficients of the equation.